Nilai-Nilai Pendidikan dalam Kesenian Kompang di Kelurahan Rimba Sekampung Kecamatan Bengkalis - Syahira Baharuddin, Nilam; Ratna Suri, Dian; Rahmadani, Novita (Sekolah Tinggi Agama Islam (STAI) Al- Kifayah Riau, 2023)
Kompang art is art that refers to Islamic values ​​which basically express praise to Allah SWT as well as blessings and greetings to the Prophet Muhammad SAW. In this paper, the author is interested in discussing the educational values ​​contained in the Kompang art in Rimba Sekampung Village. The method used is descriptive qualitative by conducting interviews with one of the informants, namely Juliono as the leader of the Kompang arts, Rimba Sekampung village. Then do an analysis that this Kompang art has educational values ​​in it which are contained in the chanting of blessings from the book al Barzanji. The educational values ​​contained in the Kompang arts prayer include faith values, worship values, and moral values